The frequency of hypothyroidism and its relationship with HCV positivity in patients with thalassemia major in southern Iran - Haghpanah, Sezaneh; Jelodari, Shohreh; Karamifar, Hammdollah; Saki, Forough; Rahimi, Rahil; De Sanctis, Vincenzo; Dehbozorgian, Javad; Karimi, Mehran (Acta Biomedica Atenei Parmensis, 2018)
Introduction: Hypothyroidism is one the most complication due to iron overload in patients with β-thalassemia major (TM). On the other hand these patients are prone to Hepatitis C virus (HCV) infection that can cause  thyroid dysfunction by itself or as the side effect of treatment with interferon (INF) or IFN plus ribavirin. The aim of this study is to evaluate the association of hypothyroidism with HCV positivity and serum ferritin levels in patients with TM. Methods: In this cross-sectional study, 201 randomly selected patients with TM who were registered at the Thalassemia Clinic of a tertiary hospital in Shiraz, southern Iran were investigated. Thyroid function tests and serologic screening assays for HCV seropositivity (HCV Ab and HCV-RNA) were conducted for all patients. Results: Frequency of hypothyroidism was 22.9% including 19.9% subclinical hypothyroidism, 2% primary overt hypothyroidism and 1% central hypothyroidism. Eighty six patients (42.8%) were HCV Ab positive and 60 patients (29.9%) were HCV RNA positive. No significant relationship was found between hypothyroidism and HCV positivity or receiving IFN-α (P>0.05). Hypothyroidism showed a borderline significant association with high serum ferritin levels in TM patients (P=0.055). Conclusion: Our results showed no significant association between hypothyroidism and HCV infection in TM patients. It seems that the main mechanism of hypothyroidism in our patients is iron overload; however, for better evaluation a larger multicenter study is recommended.  Also due to the importance of consequences of HCV infection, more careful pre-transfusional screening of blood should be considered in TM patients.